Factors Influencing The Development Of The Accounting Role In Society - Bastian, Indra (The International Journal of Accounting and Business Society, 2007)
The objective of the paper is to discuss factors influencing the development of the accounting role in society. The discussions focus on reasons why a study of the factors that influence the development ofÂ  the accounting role is needed. The paper concludes that the factors influence the development of the accounting role led to ways of understanding individualsâ€™ perceptions of the accounting role over time. Related to these factors, the development of the accounting role can be classified into three periods: 1930s, 1970s, and 1990s.